2014
DOI: 10.1128/jvi.03245-13
|View full text |Cite
|
Sign up to set email alerts
|

High-Multiplicity HIV-1 Infection and Neutralizing Antibody Evasion Mediated by the Macrophage-T Cell Virological Synapse

Abstract: Macrophage infection is considered to play an important role in HIV-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 62 publications
2
113
0
Order By: Relevance
“…A similar inhibition was previously observed between cellfree and HIV-1 transfer from MoDC to CD4 T cells (31) and confirmed in this study. Interestingly, a similar inhibitory activity of VRC01 was recently reported for the HIV-1 transmission from macrophages to T cells (43). In contrast, Abela et al and Sagar et al found that VRC01 did not block cell-mediated HIV-1 transmission from HIV-1-infected PBMC or mature MoDC to TZM-bl target cells and proposed that cell-to-cell transmission enabled HIV-1 to evade inhibition by anti-gp120 Ab (44,45).…”
mentioning
confidence: 86%
“…A similar inhibition was previously observed between cellfree and HIV-1 transfer from MoDC to CD4 T cells (31) and confirmed in this study. Interestingly, a similar inhibitory activity of VRC01 was recently reported for the HIV-1 transmission from macrophages to T cells (43). In contrast, Abela et al and Sagar et al found that VRC01 did not block cell-mediated HIV-1 transmission from HIV-1-infected PBMC or mature MoDC to TZM-bl target cells and proposed that cell-to-cell transmission enabled HIV-1 to evade inhibition by anti-gp120 Ab (44,45).…”
mentioning
confidence: 86%
“…Whether the MOIs in a leaf follow a multimodal distribution in other plant viruses could be tested using a combination of in situ approaches, as we did in this work. Beyond plant viruses, current data on HIV also suggest a multimodal distribution of the MOIs depending on the infection route, with a low MOI when the infection takes place from cell-free virus and a high MOI during cell-to-cell virus transfers (48).…”
Section: Discussionmentioning
confidence: 99%
“…Several different techniques have been used to distinguish target cells from effector cells, such as labeling of cells with fluorescent dyes (21) or mechanical separation of cells by the use of transwells or by continuous shaking of mixed cells (31). However, each of these approaches has its issues.…”
Section: Discussionmentioning
confidence: 99%